Peroxisome Proliferator-Activated Receptor Gamma (PPARG2) rs3856806 Gene Polymorphism as a Risk Factor for Type 2 Diabetes Mellitus - Fauzaan Azhar Rizqulloh; Donny Nauphar; Tiar Masykuroh Pratamawati (GHMJ (Global Health Management Journal), 2026)
Background: Diabetes Mellitus (DM) is a long-term metabolic illness brought on by either insufficient or inefficient insulin production by the pancreas. Worldwide, 537 million adults between the ages of 20 and 79 are thought to have DM. Genetics is one of the risk factors involved in the pathophysiology of type 2 DM. The gene encodes PPARG2 protein, a group of proteins that are part of the core receptor in carbohydrate and lipid metabolism. Among the two isoforms, PPARG2 is specific to adipose tissue and plays an important role in adipogenesis and mediating insulin sensitivity. Aims: This study aims to examine the PPARG2 rs3856806 gene polymorphism as a risk factor for the occurrence of type 2 diabetes mellitus in the Cirebon population. Methods: This case-control study involved 30 cases of type 2 DM and 30 healthy controls. Data were obtained with blood sugar level test, DNA extraction, and PCR-RFLP with Eco72I restriction enzyme, followed by visualization of results using gel electrophoresis. Results: The C Allele frequency was higher in the case group (76.6%) while the T Allele frequency was higher in the control group (56.6%). The CT heterozygote genotype frequency was more common in the control group (86.7%) and the TT homozygous mutant genotype frequency was higher in the case group (3%) compared to the control group (0%). The results of the Chi-Square Test obtained a p-value of 0.001 with an OR value of 0.118 (CI95%=0.033-0.422). Conclusion: The PPARG2 rs3856806 polymorphism was significantly associated with lower odds of type 2 diabetes mellitus in the population of Cirebon, Indonesia, when analyzed under a dominant genetic model comparing T-allele carriers (CT + TT) to non-carriers (CC).